Effects of Customer Relationship Management on Customer Loyalty of Mazda Dealer in Nakhon Phanom - Teekathananont, Paramaporn; Ketchompu, Daranee (Ph.D. in Social Sciences Journal, 2024)
This research article aims to study to investigate the relationship and effects of customer relationship management and customer loyalty. The research is employed quantitative method. The data collection was conducted with customers of Mazda dealer in Nakhon Phanom, 212 completed questionnaires mailed survey were used for data analyses. Furthermore, the statistic testing was used percentage, mean, standard deviation, and multiple correlation analysis, while multiple regression analysis for the hypotheses testing. Findings are as follows: (1) Customer relationship management in relationship with referrals and influencer groups in purchasing decision aspect affects customer loyalty, and (2) customer relationship management in the customer view of value aspect affects customer loyalty.